2021
DOI: 10.1101/2021.11.01.21265764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equipment-free detection of SARS-CoV-2 and Variants of Concern using Cas13

Abstract: The COVID-19 pandemic, and the recent rise and widespread transmission of SARS-CoV-2 Variants of Concern (VOCs), have demonstrated the need for ubiquitous nucleic acid testing outside of centralized clinical laboratories. Here, we develop SHINEv2, a Cas13-based nucleic acid diagnostic that combines quick and ambient temperature sample processing and lyophilized reagents to greatly simplify the test procedure and assay distribution. We benchmarked a SHINEv2 assay for SARS-CoV-2 detection against state-of-the-ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The latter can achieve remarkably low LODs due to its capability of trans-cleaving approximately 10 4 (re)RNA molecules in its vicinity upon activation by recognition of the target sequence 60 . Nevertheless, most methods developed for the detection of SARS-CoV-2 genes employ either reverse transcription loop-mediated isothermal amplification (RT-LAMP; LOD: 100 copies/µl, 90 min sample-to-result time 61 ) or reverse transcription recombinase polymerase amplification (RT-RPA; LOD: 2.5-100 copies/µl, sample-to-result-time: 20 min - 1 hour 42,62,63 ) as a target-amplification strategy or even both (LOD: 82 copies/µl after ca. 50 min 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter can achieve remarkably low LODs due to its capability of trans-cleaving approximately 10 4 (re)RNA molecules in its vicinity upon activation by recognition of the target sequence 60 . Nevertheless, most methods developed for the detection of SARS-CoV-2 genes employ either reverse transcription loop-mediated isothermal amplification (RT-LAMP; LOD: 100 copies/µl, 90 min sample-to-result time 61 ) or reverse transcription recombinase polymerase amplification (RT-RPA; LOD: 2.5-100 copies/µl, sample-to-result-time: 20 min - 1 hour 42,62,63 ) as a target-amplification strategy or even both (LOD: 82 copies/µl after ca. 50 min 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the miSHERLOCK variant assay uses LbCas12a (NEB) with RPA pre-amplification to detect N501Y, E484K and Y144Del covering eight lineages (WA-1, Alpha, Beta, Gamma, Eta, Iota, Mu and Zeta) and was tested only on contrived samples (RNA spiked into human saliva) 21 . The SHINEv2 assay uses LwaCas13a with RPA pre-amplification to detect 69/70Del, K417N/T, L452R and 156/157Del + R158G covering eight lineages (WA-1, Alpha, Beta, Gamma, Delta, Epsilon, Kappa and Mu) and was tested with only the 69/70Del gRNAs on 20 Alpha-positive NP clinical samples 49 . Finally, the mCARMEN variant identification panel (VIP) uses 26 crRNA pairs with either the LwaCas13a or LbaCas13a and PCR pre-amplification to identify all current circulating lineages including Omicron; however, the VIP requires the Fluidigm Biomark HD system or similar, more complex instrumentation for streamlined execution 50 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the miSHERLOCK variant assay uses LbCas12a (NEB) with RPA preamplification to detect N501Y, E484K and Y144Del covering eight lineages (WA-1, Alpha, Beta, Gamma, Eta, Iota, Mu and Zeta) and was tested only on contrived samples (RNA spiked into human saliva) 21 . The SHINEv2 assay uses LwaCas13a with RPA pre-amplification to detect 69/70Del, K417N/T, L452R and 156/157Del + R158G covering eight lineages (WA-1, Alpha, Beta, Gamma, Delta, Epsilon, Kappa and Mu) and was tested with only the 69/70Del gRNAs on 20 Alpha-positive NP clinical samples 49 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent reports have focused on variant panels designed to target a finite number of emergent mutations to discern variant identity, particularly in the first months of 2021. Most panels utilize RT-PCR or novel isothermal technologies (e.g., RT-LAMP, CRISPR/Cas-based, massspectrometry) to target specific polymorphisms in the S gene that have been ascribed to each of these variants 25,27,45,[48][49][50] . However, a recent deep analysis of circulating variants across the globe revealed that most of these signature mutations are not under positive selection 1 .…”
Section: Discussionmentioning
confidence: 99%